Not all incentives wash out the warm glow: The case of blood donation revisited - Joan Costa-Font; Mireia Jofre-Bonet; Steven T. Yen (Center for Economic Studies and ifo Institute (CESifo), 2011)
The issue of the nature of the altruism inherent in blood donation and the perverse effects of financial rewards for blood and/or organ donation has been recently revisited in the economic literature with limited consensus. As Titmuss (1970) famously pointed out, providing monetary incentives to blood donors may crowd out blood supply as purely altruistic donors may feel less inclined to donate if a reward is involved - in addition to having the effect of reducing blood quality. In this paper we take a different approach by focusing on the nature of the rewards. That is, we examine how favouring different types of incentives are related to the likelihood of donating blood by exploiting a large sample representative of 15 European countries in 2002. Our results show that donors are less likely to favour monetary rewards for blood donation but are more likely to favour non-monetary ones. This is consistent with the idea that while monetary rewards may crowd out blood donation, non-monetary rewards do not.
Keywords: H10; J18; 330; altruism; blood donation; incentives; nudging; recursive system; warm glow; Blutspendedienst; Altruismus; Ökonomischer Anreiz; Crowding out; Europa